How Market Power Affects Potential Bankruptcy Post and During COVID-19: Does Sharia Rural Bank Soundness Matter? - Fajri, Moh Najikhul (Journal of Southeast Asian Islam and Society, 2023)
The COVID-19 pandemic has forced banks to participate in increasing their capacity to accommodate consumers and producers so that there are no prolonged shocks. Sharia rural bank is a type of community bank that can directly contribute to the village level. For this reason, this study aims to analyze the effect of market power on the potential bankruptcy for banking before and after the COVID-19 pandemic by involving banking indicators. The data used in this study is a panel of 113 sharia rural banks throughout Indonesia during 2013-2021. The results show that market forces have a positive effect on banking stability. Meanwhile, equities and economic growth are alleged to be part of the decline in bank risk. When COVID-19 hit, banks found a prolonged crowding out effect due to the absence of financing absorption by consumers. So that it has the opportunity to increase financing for banks that are above the profitability standard.